Optimizing the management of Surya Tidar Tofu Chips SMEs, Kalijoso Village, Magelang Regency - Marlina Kurnia; Risa Dewi Ambarwati; Aishah Norzianawati; Reiza Rizky Nasywa Salsabilla; M. Dienan Hadyan Hanif; Maulida Rizka Afifa (Universitas Muhammadiyah Magelang, 2022)
The purpose of this community service is to increase the competitiveness of MSMEs through the management of the Surya Tidar Tofu Chips business. The development of the food product business from MSMEs is supported by several things, such as partners who already have the skills to produce creative products in the form of tofu chips and are of productive age. This program begins with socialization, training and mentoring. The result of this program is an increased understanding of the importance of digital marketing by utilizing social media, improving packaging with its own brand, repairing signboard and simple bookkeeping to track business development.